Model Integratif Perlindungan Konsumen Berbasis Maqāṣid Syariah di Indonesia - R, Randy; H, Herianti; Masse, Rahman Ambo; Sapa, Nasrullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the legal aspects of consumer protection from the perspective of Islamic economic law in Indonesia. Consumer rights protection is increasingly complex due to the rise of digital transactions and the growing halal industry. Although consumer protection is regulated under Law No. 8 of 1999, it does not fully reflect the core principles of fiqh muamalah, such as justice, transparency, and the avoidance of gharar. This research employs a normative juridical approach using both statute and conceptual methods to examine the relationship between positive law and Islamic principles. The findings indicate a gap between current regulations and sharia values, emphasizing the need for regulatory harmonization. In conclusion, consumer protection in Islamic economic law should align with maqashid sharia and promote ethics-based supervision through institutional reinforcement.